Developing food, water and energy nexus workflows - Ian McCallum; Carsten Montzka; Bagher Bayat; Stefan Kollet; Andrii Kolotii; Nataliia Kussul; Mykola Lavreniuk; Anthony Lehmann; Joan Maso; Paolo Mazzetti; Aline Mosnier; Emma Perracchione; et al. (International Journal of Digital Earth, 2020)
There is a growing recognition of the interdependencies among the supply systems that rely upon food, water and energy. Billions of people lack safe and sufficient access to these systems, coupled with a rapidly growing global demand and increasing resource constraints. Modeling frameworks are considered one of the few means available to understand the complex interrelationships among the sectors, however development of nexus related frameworks has been limited. We describe three open-source models well known in their respective domains (i.e. TerrSysMP, WOFOST and SWAT) where components of each if combined could help decision-makers address the nexus issue. We propose as a first step the development of simple workflows utilizing essential variables and addressing components of the above-mentioned models which can act as building-blocks to be used ultimately in a comprehensive nexus model framework. The outputs of the workflows and the model framework are designed to address the SDGs.